Perceptions of Classroom Working Alliance and Student Performance - Toste, Jessica R.; Heath, Nancy; Dallaire, Lynn (Alberta Journal of Educational Research, 2011)
Positive teacher-student relationship has been established as an important contributor to students' social, behavioral, and academic adjustment. Nevertheless, current research has not employed relationship measures that examine both teachers' and students' perceptions. Furthermore, the measures currently being used lack breadth in the definition of the teacher-student relationship. Using the construct of "working alliance" from counseling psychology, this study investigated teachers' (n=14) and elementary school students' (n=53) perceptions of their working alliance and explored how this construct relates to student performance. Teachers' and students' ratings on subscales of the Classroom Working Alliance Inventory (CWAI) were found to be significantly related to one another. In addition, regression analyses demonstrated that both teachers' and students' ratings of working alliance contributed significantly to ratings on the Student Performance Questionnaire (SPQ). Un rapport positif entre l'enseignant et l'élève s'est avéré être un facteur important qui contribue à l'adaptation sociale, comportementale et académique des élèves. Néanmoins, la recherche actuelle n'a pas employé de mesures des rapports qui examinent à la fois les perceptions des enseignants et celles des élèves. De plus, les mesures actuelles manquent d'envergure quant à leur définition du rapport enseignant-élève. Empruntant de la psychologie thérapeutique la construction de l'alliance de travail, nous avons étudié les perceptions qu'ont les enseignants (n=14) et les élèves de l'élémentaire (n=53) de leur alliance de travail et avons examiné dans quelle mesure cette construction joue un rôle dans le rendement des élèves. Nous avons trouvé une relation significative entre les cotes des enseignants et celles des élèves aux sous-échelles de l'inventaire de l'alliance de travail en salle de classe (Classroom Working Alliance Inventory). De plus, les analyses de régression ont démontré que ces cotes, tant celles des enseignants que celles des élèves, ont contribué de façon significative aux cotes du questionnaire sur le rendement des élèves.